AERONET versus MODIS aerosol parameters at different spatial resolutions over South-East Italy - SANTESE, MONICA; DE TOMASI, Ferdinando; PERRONE, Maria Rita (2007)
Aerosol parameters retrieved by Aerosol Robotic Network (AERONET) Sun photometer measurements at the Physics Department of Lecce's University (40°20′N, 18°6′E) are compared to similar Moderate Resolution Imaging Spectroradiometer (MODIS) data retrieved at different spatial resolutions colocated in space and time to contribute to the validation of MODIS aerosol products over southeast Italy and to investigate the correlation dependence on spatial resolution and identify regional biases of Lecce's AERONET data. In particular, MODIS aerosol optical depths retrieved at 550 nm over ocean and over land-ocean for window sizes of 50 × 50, 100 × 100, and 300 × 300 km2 centered on the AERONET monitoring site are correlated to AERONET aerosol optical depths colocated in time. It is shown that correlation factors of linear regressions span the 0.88–0.83 range and weakly tend to reduce with window size. In addition, MODIS aerosol optical depths meet expected uncertainties, and the percentage of data points within expected uncertainties is not affected by the window size. Slope and intercept values of linear regressions fitting over ocean aerosol optical depths are instead different than those fitting over land-ocean aerosol optical depths and are dependent on window size. The observed dependence is analyzed and discussed in the paper. Finally, it is shown that the paper's results can allow inferring that the tested AERONET aerosol parameters can be considered representative, at least, of a ∼300 × 300 km2 southeast Italy area centered on the Lecce's AERONET site.